Analyzing The Effect of Social Media Influencer on Purchase Intention Through Parasocial Relationships: The Moderation Role of Influencer-Product Congruency - Weni Trisnawati; Helma Malini; Wenny Pebrianti; Ramadania Ramadania; Heriyadi Heriyadi (eCo-Fin, 2025)
The rapid expansion of social media platforms has led to continuous transformations in marketing approaches and methodologies. Among contemporary promotional techniques, influencer marketing has emerged as a pioneering strategy. This development necessitates brands and marketing professionals to carefully select appropriate social media personalities. The research examines how influencers' intimate self-disclosure and self-influencer congruence affect consumer purchasing intention, with particular attention to the intermediary function of parasocial relationships and the potential moderating effect of influencer-product congruency. The investigation employed quantitative methodologies, gathering data from 213 survey participants. Research propositions were assessed through partial least squares structural equation modelling (PLS-SEM), utilizing SmartPLS v.4.1 analytical tools. Results indicate parasocial relationships are an intermediary mechanism linking influencers' intimate self-disclosure and self-influencer congruence to purchase intention. However, the findings challenge initial expectations by demonstrating that the correlation between influencer-product congruency does not significantly modify the connection between parasocial relationships and purchase intention. These discoveries aim to contribute fresh perspectives to the understanding of social media personalities' effectiveness in influence-based marketing strategies.